The dynamic factor model revisited: the identification problem remains - Terje Skjerpen (Statistics Norway, Research Department, 2004)
The lack of identification of short run run effects in a system of regression equations consisting of a dynamic translog cost function and cost share equations derived from this cost function is shown.
Keywords: C32; D21; 330; Dynamic cost function